Metode Nuclear Magnetic Resonance Sounding (NMRS) Merupakan Teknik Baru dalam Eksplorasi Airtanah - Nurdin, Muhammad; Sudarto, Slamet (EKSPLORIUM, 2011)
NMRS method has been used in the past 10 years with success in various geological context and groundwater exploration. This method has indeed the ability of directly detecting the presence of water through the excitation of the hydrogen protons of water molecules. The frequency to which the H protons react depends on the magnitude of the Earth magnetic field, while the intensity of the excitation determines the depth of investigation. The amplitude of the magnetic field generated in return by the water of a layer is proportional to the porosity of this layer, and the time constant of the relaxation curve is linked to the mean pore size of the material, that is to say tightly related to its hydraulic permeability. A field cases such as illustrate NMRS application that is taken from measurement at Mauritania. NMRS measurement results in dry areas indicate the time-relaxation amplitude is low (10 A-ms) and water content is 1%. While the results of the aquifer region NMRS measurements showed -relaxation-time amplitude is quite large (270 A-ms) and water content is 12-30%.